A Novel Approach of Controlling the Solar PV Integrated Hybrid Multilevel Inverter - Sunita Kumari; Sudhir Y. Kumar (IAES Indonesian Section, 2018)
The part of renewable energy systems like solar photovoltaic (PV) and wind power generation (WPG) is playing an energetic role in energy production. The power electronics technology growths have directed to the progresses in the solar power generation and solar PV sources have the potential to progress one of the key providers to the upcoming electricity. Lower voltage rating of solar PV systems requires a high voltage progress converter for parts grid associating with a DC-AC inverter. The solar energy acquired from the solar panel varies with times and solar irradiation. The boost DC/DC converter is used to sustain the constant output voltage achieved from the solar panel using MPPT algorithm and is operated according to the requirement. A 1-Ф cascade 13-level inverter is used to produce 13-level output voltage from the DC supply voltage achieved from PV panels. It offers better-quality sinusoidal output voltage and current waveforms and lower total harmonic distortion. In this paper, the proposed model is designed and the results are verified through simulation using MATLAB/SIMULINK tools